2015
DOI: 10.1007/s11368-015-1188-1
|View full text |Cite
|
Sign up to set email alerts
|

Degradation study of mesotrione and other triketone herbicides on soils and sediments

Abstract: Purpose Triketone compounds are considered to be less stable in the ecosystems in comparison with other herbicides. However, their degradation processes in environment are under investigation as both parents and degradation products can exhibit toxicity on non-target organisms. The objective of this research was to investigate the degradation of triketone herbicides: mesotrione, sulcotrione, and tembotrione, as well as their degradation products in soils and sediments. Materials and methods The degradation stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 35 publications
3
30
0
1
Order By: Relevance
“…Lavieille et al [58] demonstrated the utility of evaluating the stability of a pesticide towards sunlight when applied on crops, and highlighted the quick photolytic transformation of formulated mesotrione compared to pure mesotrione. In their study, the mesotrione rate of photolysis on leaves was much higher compared with data from the literature in water and on soils which implies that photolysis is likely to be a fast dissipation process on crops, as confirmed later by Barchanska et al [59]. Moreover, mesotrione on wax films imitating the surface of leaves is very reactive, with a DT 50 of photolysis of 2 h [60].…”
Section: Abioticmentioning
confidence: 77%
“…Lavieille et al [58] demonstrated the utility of evaluating the stability of a pesticide towards sunlight when applied on crops, and highlighted the quick photolytic transformation of formulated mesotrione compared to pure mesotrione. In their study, the mesotrione rate of photolysis on leaves was much higher compared with data from the literature in water and on soils which implies that photolysis is likely to be a fast dissipation process on crops, as confirmed later by Barchanska et al [59]. Moreover, mesotrione on wax films imitating the surface of leaves is very reactive, with a DT 50 of photolysis of 2 h [60].…”
Section: Abioticmentioning
confidence: 77%
“…The maximum concentration of AMBA (29 μg/L) was determined in March, and then it was slowly decreased to 18 μg/L at 6 months. This slow decrease in the AMBA concentration was due to the slow exchange of water between the pond and its tributaries and the highest stability of this compound in environment among all investigated triketones and their degradation products (Table 1; Barchanska et al 2016). MNBA was determined in water from the drainage ditch at a concentration of 147 μg/L (sample collected in April).…”
Section: Discussionmentioning
confidence: 96%
“…The detailed procedure for triketone extraction from soil and sediment samples is described in Barchanska et al (2016). Briefly, soil and sediment samples (10 g) were mixed with acetonitrile (30 mL) and shaken for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…In the soil, this herbicide can be absorbed by the roots of the plants and translocated via xylem and phloem. It presents water solubility of 28 g L -1 at pH = 7 and pK a = 3.2 (Barchanska et al, 2016). It is an herbicide from the triketone group and its mechanism of action is the inhibition of the enzyme 4-hydroxyphenyl-pyruvate-dioxygenase; it inhibits the formation of carotenoids, which are responsible for the protection against the excessive energy generated by the absorption of light into the leaf.…”
Section: Introductionmentioning
confidence: 99%